PROBLEMS IN THE FIELD OF GRAIN PROCESSING TECHNOLOGICAL PROCESSES AND IMPROVEMENT OF THEIR PREVENTION MEASURES (British Journal of Global Ecology and Sustainable Development, 2022)
Based on the expediency of using an image impact machine for grinding grain and grain, it simplifies the technological process, improves their quality and increases its stability during storage. It increases the importance of the scientific basis and structure of the universal technology of flour production with high productivity and quality.